Behavioral and cortical mechanisms for spatial coding and action planning - Medendorp, W. Pieter; Beurze, Sabine M.; Van Pelt, Stan; Van Der Werf, Jurrian (Cortex, 2008)
There is considerable evidence that the encoding of intended actions in visual space is represented in dynamic, gaze-centered maps, such that each eye movement requires an internal updating of these representations. Here, we review results from our own experiments on human subjects that test the additional geometric constraints to the dynamic updating of these spatial maps during whole-body motion. Subsequently, we summarize evidence and present new analyses of how these spatial signals may be integrated with motor effector signals in order to generate the appropriate commands for action. Finally, we discuss neuroimaging experiments suggesting that the posterior parietal cortex and the dorsal premotor cortex play selective roles in this process.